Edge computing offloading policies and resource allocation considering system fairness in trusted environments - Shouyi YANG; Fukang LI; Ruimin REN (Tongxin xuebao)
Considering the fairness problem in edge computing in an unreliable trust environment, the offloading decision and resource allocation problem of edge computing was studied for a multi-user multi-server scenario.Based on the proposed real-time trust model, system fairness was defined from the perspective of user satisfaction, a joint optimization model considering trust and fairness was established, and a trust-based task offloading and resource allocation (TOA) algorithm was proposed on this basis.The original NP-hard problem was converted into multiple deterministic optimization subproblems, the offloading strategy was determined based on the backtracking algorithm, and the optimization of resource allocation was accomplished by using the Lagrange multiplier method, the convex optimization toolbox, and the bifurcated iterative search method, so as to achieve system fairness and enhance user satisfaction.Simulation experimental results show that the proposed algorithm outperforms other benchmark algorithms.